Some Die Young: A Follow-Up Study of Young Men Exposed to Violence in Sweden - Trygged, Sven (Victims & offenders, 2021)
This register-based study from Sweden examines mortality risks among young male victims of violence. In total, 8722 men aged 18–24 years who spent at least one night in inpatient care after exposure to violence in the years 1992–2005 were compared with 78,702 age-matched men from the general population. Cox regressions showed that men exposed to violence had a >3 times higher risk of all-cause mortality, a >4 times higher risk of suicide, and about a 20 times higher risk of death from later violence. The risk of suicide remained stable during the follow-up, and the risk of all-cause mortality and death from later violence decreased.Abbreviations: NBHW: The Swedish National Board of Health and Welfare (Socialstyrelsen); Brå: The Swedish National Council for Crime Prevention (Brottsförebyggande rådet)